Aquaporin‐2 plays an important role in water transportation through the bladder wall in rats. Issue 8 (24th May 2018) - Morizawa, Yosuke; Torimoto, Kazumasa; Hori, Shunta; Gotoh, Daisuke; Nakai, Yasushi; Miyake, Makito; Hirayama, Akihide; Tanaka, Nobumichi; Fujimoto, Kiyohide
Abstract : Aim: We investigated the role of the bladder wall in permeating water, focusing on aquaporins. Methods: Female Sprague‐Dawley rats weighing 300 g were used to investigate the role of the bladder wall in saline permeation. Changes in intravesical fluid volume and sodium concentration were measured in the desmopressin acetate hydrate‐loaded and control groups 3 h after administration. Bladders were resected to measure aquaporin‐1, 2, and 3 gene expression using qRT‐PCR. Additionally, the change of aquaporin‐2 expression was measured using Western blotting and immunohistochemistry in intravesical aquaporin‐2 siRNA‐treated and control groups. Results: Although the intravesical fluid volume and sodium concentration significantly decreased from 0 to 3 h (1.00 ± 0.00 vs 0.83 ± 0.08 mL, 157.80 ± 1.30 vs 146.8 ± 1.92 mEq/mL, P  < 0.01, respectively in the control group), administration of desmopressin did not affect the extent of volume change. Aquaporin‐2 expression was significantly higher in the 3‐h distended bladders than in the empty bladder. Aquaporin‐2 siRNA treatment suppressed aquaporin‐2 expression and the change of intravesical fluid volume from 0 to 3 h (1.00 ± 0.00 and 0.99 ± 0.02 mL), which was related to the suppression of sodium concentration change in comparison with control siRNA treatment (149.6 ± 2.4 vs 143.6 ± 3.67 mEq/mL, P  < 0.05). Conclusions: The rat urinary bladder absorbs water and salts under the full‐filled condition. Aquaporin‐2 plays an important role in the transport of water, accompanied by sodium concentration change. We demonstrated a part of the bladder absorption mechanism, which may lead to development of a new method for regulating bladder storage function.